Review of Developments in Electronic, Clinical Data Collection, and Documentation Systems over the Last Decade – Are We Ready for Big Data in Routine Health Care? - Kessel, Kerstin A.; Combs, Stephanie E. (Frontiers in Oncology, 2016)
Recently, information availability has become more elaborate and wide spread, and treatment decisions are based on a multitude of factors including imaging, molecular or pathological markers, surgical results and patient’s preference. In this context the term “Big Data” evolved also in health care. The “hype” is heavily discussed in literature. In interdisciplinary medical specialties, such as radiation oncology, not only a heterogeneous and voluminous amount of data must be evaluated, it is also spread in different styles across various information systems. Exactly this problem is also referred to in many ongoing discussions about Big Data - the “three V’s”: volume, velocity, and variety. We reviewed 895 articles extracted from the NCBI databases about current developments in electronic clinical data management systems and their further analysis or post-processing procedures. Few articles show first ideas and ways to immediately make use of collected data, particularly imaging data. Many developments can be noticed in the field of clinical trial or analysis documentation, mobile devices for documentation and genomics research. Using Big Data to advance medical research is definitely on the rise. Health care is perhaps the most comprehensive, important and economically viable field of application.